Starch granules from human teeth: New clues on the Epi-Jomon diet - Shibutani, Ayako; Aono, Tomoya; Nagaya, Yukihito (Frontiers in Ecology and Evolution, 2022)
This study examined starch granules from the dental calculus of specimens from the Epi-Jomon (Zoku-Jomon in Japanese, ca. 350 BCE–350 CE) period in Japan for taxonomic identification of plant food items and the reconstruction of human socioeconomic practices. Dental calculus was extracted from 21 individuals across six Epi-Jomon sites in Hokkaido. Moreover, 12 starch granules and starch clusters were recovered from nine individuals. The morphologies of the extracted starch granules were then classified into five types: elliptical, angular circular, polygonal, pentagonal, and damaged. Morphometric analysis indicated that a small portion of these starch granules may have derived from acorns, nuts, and bulb or tuber plants, with one starch granule supposedly from rice. Although extracted starch granules are poor predictors of food diversity at the individual level, the results can identify potential food sources of the surveyed population. This is the first study to determine how well plant microremains in dental calculus reflect a plant diet in the Epi-Jomon population. The starch granules discovered at the surveyed sites provide essential information about the utilization of plant species and cultural contacts in Hokkaido during this period. This is of great significance in reconstructing the Epi-Jomon subsistence patterns in Hokkaido and exploring cultural interactions between hunting-gathering-fishing and agrarian societies.